Գիտության ոլորտում հայ-ֆրանսիական համագործակցությունը 1992-2013 թթ. - Բաղդասարյան Տիգրան (YSU Journal of International Affairs, 2014)
This paper analyzes the legal basis, main directions and existing obstacles, as well as possible perspectives of bilateral cooperation between the Republic of Armenia and the French Republic in the sphere of science. Being a weak link in the Armenian-French cultural, educational and scientific relations, scientific cooperation between Armenia and France has developed rather slowly. However, since 2008 the cooperation in this sphere has fixed a positive shift, which was determined by new agreements and increased attention to the issue by Armenia and France.